Analysis of Consumer Purchase Intentions on Matahari.com in DKI Jakarta - Tiara Septiani (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to analyze consumer purchase intention at Matahari.com by adopting the dimensions of purchase intention, namely transactional intention, referential intention, preferential intention and explorative intention. Based on these four dimensions to determine consumer purchase intention at Matahari.com in DKI Jakarta. This study uses a quantitative approach with a survey method. This study uses one variable, namely purchase intention. This study uses two data analysis techniques, namely descriptive analysis and average scores. This study uses validity tests and reliability tests as research instrument tests. In this study, the tool used to process data is SPSS 29 software. The population and sample in this study were 200 respondents who knew about Matahari.com and were domiciled in DKI Jakarta using the non-probability sampling method, namely quota sampling. The distribution of questionnaires was carried out online using Google Form media. This study began in January 2024 and the distribution of questionnaires was carried out in July 2024. Of the four dimensions of consumer purchase intention, the explorative intention dimension has the highest percentage value in consumer purchase intention to make purchases at Matahari.com.